Comparison of Human Metapneumovirus Findings with Other Respiratory Tract Viruses in Children with Bronchiolitis - Altay, Derya; Uzum, Kazim; Kose, Mehmet; Gokahmetoglu, Selma; Yikilmaz, Ali (Galenos Yayincilik, 2018)
INTRODUCTION: Acute bronchiolitis is a lower respiratory tract disease, often seen in children caused by viral agents. The aim of this study is to determine viral agents in particular the prevalence of Human Metapneumovirus in children diagnosed with acute bronchiolitis in our region and to evaluate clinical, laboratory and radiological findings of these patients. METHODS: The prevalence of Respiratory Syncytial Virus, Parainfluenza Virus, Adenovirus and Human Metapneumovirus were investigated in 73 children at one month-two-years of age diagnosed with acute bronchiolitis in pediatric emergency clinic between November 2006 and May 2007. Clinical, laboratory and radiological findings of these patients were evaluated. RESULTS: The prevalence of Human Metapneumovirus 5,4%, Respiratory Syncytial Virus 75%, Parainfluenza Virus 5.4% and Adenovirus 6.8% were determined in patients diagnosed with acute bronchiolitis. Respiratory Syncytial Virus and Human Metapneumovirus were found together in only one patient. Clinical and radiological findings of patients with Human Metapneumovirus positivity were similar to patients with other viral agents of bronchiolitis. Any viral agent was not detected in 16,4% of patients. 67% of patients with virus positive and also 67% of patients with Respiratory Syncytial Virus positive were treated with antibiotics. DISCUSSION and CONCLUSION: Clinical and radiological findings of Human Metapneumovirus are similar to other viral agents of bronchiolitis. At least one viral agent was detected in the etiology of disease in 83,5% of patients diagnosed with acute bronchiolitis. However, antibiotic treatment took place in the majority of the patients. Therefore, preventing the unnecessary use of antibiotics in these patients will reduce the development of antibiotic resistance and hospital costs.
Bronşiolit tanısı alan çocuklarda human metapnömovirüs bulgularının diğer solunum yolu virüsleri ile karşılaştırılması
Keywords: acute bronchiolitis; antibiotic; Human Metapneumovirus; pediatrics